2014
DOI: 10.1016/j.bone.2014.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Type VII collagen is enriched in the enamel organic matrix associated with the dentin–enamel junction of mature human teeth

Abstract: The inner enamel region of erupted teeth is known to exhibit higher fracture toughness and crack growth resistance than bulk phase enamel. However, an explanation for this behavior has been hampered by the lack of compositional information for the residual enamel organic matrix. Since enamel-forming ameloblasts are known to express type VII collagen and type VII collagen null mice display abnormal amelogenesis, the aim of this study was to determine whether type VII collagen is a component of the enamel organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 38 publications
2
24
0
2
Order By: Relevance
“…We hypothesize that localization of both types IV and VII collagen (McGuire et al, 2014b) to this region could help explain these previously reported properties of the DEJ. By analogy with the mechanical stability of the dermal-epidermal junction in skin Immunoreactivity of type IV collagen was greatly diminished in both the cuspal and cervical regions after 6 hr of digestion with purified bacterial collagenase.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…We hypothesize that localization of both types IV and VII collagen (McGuire et al, 2014b) to this region could help explain these previously reported properties of the DEJ. By analogy with the mechanical stability of the dermal-epidermal junction in skin Immunoreactivity of type IV collagen was greatly diminished in both the cuspal and cervical regions after 6 hr of digestion with purified bacterial collagenase.…”
Section: Discussionmentioning
confidence: 70%
“…Extraction of enamel matrix proteins from additional thirdmolar tooth crowns (n = 6) was accomplished by complete decalcification of each crown, enamel surface up, for 14 days in 40 mL of 10% EDTA (7.4 pH) containing 0.002% NaN 3 at 20°C (McGuire et al, 2014b). The enamel organic matrix layer was then recovered by gentle wiping of the dentin surface with a ballpoint-applicator microbrush (Kerr Totalcare, Orange, CA, USA).…”
Section: Protein Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 a, b). There is a strong indication that these are fibers of type VII collagen which can complex with other collagens and may contribute to the structural resilience of enamel and play a role in bonding enamel to dentin [4].Crystals of hydroxyapatite in human enamel are long but narrow (20-80 nm in cross section); they are organized in parallel bundles, so called "enamel rods," of about 4-8 microns in diameter. Morphologically organic matrix is following the shape of these rods.…”
mentioning
confidence: 99%